ANALYSIS OF IR SPECTRA OF SILK FABRICS AND THEIR CHEMICAL PROPERTIES (Scientific journal of the Fergana State University, 2026)
By analyzing the absorption of different types of silk in the range of 1400–800 cm-1 in the IR spectra, Gly-Gly at 1015 cm-1, Ala-Ala at 970 cm-1 and absorptions at 998 and 975 cm-1 constitute the Ala-Gly bonds determined For. Also, from the bending vibrations of the IR spectrum, -OH and stretching vibrations of the C-O-C group were visible. The literature was compared and analyzed.